All Days 2008
DOI: 10.4043/19311-ms
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Methane Hydrate Concentrated Zone for Resource Assessment in the Eastern Nankai Trough, Japan

Abstract: Aiming commercialization of methane hydrate development, the Research Consortium for Methane Hydrate Resources in Japan (MH21) has been executing geological and geophysical surveys around the eastern Nankai Trough since 2001 as a national project. Interpretation and analysis studies based on 2D/3D reflection seismic surveys, multi-wells drilling campaign and other geological surveys revealed existences of methane hydrate concentrated zones, of which reservoirs were composed of turbidite sand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 0 publications
0
36
0
1
Order By: Relevance
“…12 out of these 32 wells were cored, 16 of remaining were logged with logging while drilling (LWD) tools, 1 was equipped with temperature sensors and in remaining 2 wireline tools were used for logging [37]. After this test detailed analysis of gas hydrate rich sand samples and their geophysical properties was carried out for production test [43]. Density-magnetic resonance technique used to determine gas saturation in gas reservoirs was used to estimate saturation from wireline logs [37].…”
Section: Resultsmentioning
confidence: 99%
“…12 out of these 32 wells were cored, 16 of remaining were logged with logging while drilling (LWD) tools, 1 was equipped with temperature sensors and in remaining 2 wireline tools were used for logging [37]. After this test detailed analysis of gas hydrate rich sand samples and their geophysical properties was carried out for production test [43]. Density-magnetic resonance technique used to determine gas saturation in gas reservoirs was used to estimate saturation from wireline logs [37].…”
Section: Resultsmentioning
confidence: 99%
“…Remaining indicator D higher velocity anomaly was detected in the velocity profile bottom . modified from Saeki et al, 2008 .…”
Section: Figmentioning
confidence: 99%
“…Deeper and older channels were interpreted as possible methane hydrate concentrated zones in which both of strong reflectors and high velocity anomalies were recognized. modified from Saeki et al, 2008 . International Conference on Gas Hydrates, Vancouver, Canada, 6 -10 July.…”
Section: Figmentioning
confidence: 99%
“…The stratigraphy in the Tokai-Atsumi-Kumano forearc basins was established through sequence stratigraphy and sedimentology using 2D/3D seismic, well log, and core data. It is found that a major depositional system of the sediments is a submarine fan turbidite system (e.g., [10][11][12][13][14][15]). Our target NGH reservoir is a methane hydrate-concentrated zone (MHCZ, Figure 2), which is characterized by strong amplitude and high velocity anomalies in seismic data, and the high resistivity interval in well log data (e.g., [15,16]).…”
Section: Geological Setting and Reservoir Architecture In The Second mentioning
confidence: 99%